Ictiofauna de reservatórios do semiárido como ferramenta para estimar a qualidade da água: Adaptação de um índice de integridade biótica - Nery, Gleydson Kleyton Moura (2017)
The present study aims to adapt and apply a Biotic Integrity Index (IBI) for reservoirs in the Paraíba River basin located without Brazilian semiarid, with the use of fish community sites as a subsidy. For that, 20 points were sampled in 5 reservoirs with four sample stations from July 2016 to March 2017. The IBI was obtained by elaboration and selection of metrics based on the community studied. The study was divided into two chapters. In the first one, the factors that explain the adaptive success of Oreochromis niloticus in the aquatic systems of the semiarid were oriented. It was found that the invasion ability of O. niloticus was associated with both environmental factors and biological interactions. However, there is a strong influence of environmental variables linked to these relationships, since a dissimilarity of systems regarding water quality and habitat structuring directly influence the structuring of the community in terms of composition as trophic relationships. In the second chapter, the biotic integrity index based on the fish community was proposed and applied as an environmental assessment tool for non - semiarid systems. The composition of the index was based on the metrics% native species,% endemic species,% invasive species, abundance of cichlids, abundance of species,% sp. piscivorous and% sp. intolerant An application of the index for the semiarid to the problem, the limnological state of the environment, such as total phosphorus (r² = -0.62, p <0.005), chlorophyll a (r² = -0.74, p < 05) and volume (r² = 0.33, p <0.005). The study points to a community of fish as a good indicator of environmental quality, since, during the studied period, it reduced the quality of the quality of the environment with the direct reflection in the fish community.